Effective elastic properties of granular stochastic composites under imperfect adhesion - Khoroshun, L.P.; Levchuk, O.I. (Reports of the National Academy of Sciences of Ukraine, 2017)
Proceeding from the stochastic equations of elasticity of a multicomponent composite, the effective elastic properties of a three-component composite consisting of a matrix, inclusions, and interphase porous layers are investigated. An approach, in which the three-component material is reduced to a two-component one by replacing the inclusions with the interphase layer by effective composite inclusions with equivalent or effective elastic properties, is used. Composite inclusions are modeled by a two-component matrix material, where the inclusions and the matrix have elastic moduli and volume contents according to the real inclusions and interphase layers, respectively. The curves of the dependences of the effective moduli of volume compression and shear on the volume content of inclusions and the porosity of the interphase layers are constructed.